Pendampingan Penyusunan Kompilasi Dokumen Pembinaan Umat Hindu Kabupaten Badung - Pratama, I Putu Adi; Dewi, Diah Nirmala (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
Communication Science Study Program of UHN I Gusti Bagus Sugriwa Denpasar in 2022 was given the task of carrying out community service (PKM) based on study programs as a fulfillment of the Tri Dharma Perguruan Tinggi mandatory PKM activities during this period were carried out in synergy with PHDI Badung Regency as a Hindu religious institution which is also tasked with providing information related to Hinduism and mediating institutions for Hindus. The problems found from the analysis of the PHDI situation in Badung Regency lead to the availability of a traceable archive documents of Hindus developement program that can be used to improve the PHDI of Badung Regency service programs in the future and as a guideline that can be used by Hindus, especially in Badung Regency for implementation of religious life. Therefore, assistance was carried out in compiling the compilation documents of the Hindus development program in Badung Regency by a mentoring team from the members of the PKM Communication Studies Study Program at UHN I Gusti Bagus Sugriwa Denpasar. The mentoring process is divided into two main stages, namely assistance in the management of important institutional documents and the preparation of compilation documents of the Hindus development program in Badung Regency. The data triangulation method was used during the PKM activity which included material presentation, discussion, observation of potential participants, group division, document research, document preparation, revision and editing to produce output in the form of printed book entitled "Compilation of Hindus Development Program PHDI of Badung Regency"